Eleventh IEEE European Test Symposium (ETS'06)
DOI: 10.1109/ets.2006.47
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Diagnosis of Power Switches in SOCs

Abstract: The use of power switches in modern system chips (SOCs) is inevitable as they allow for efficient on-chip static power management. Leakage is today one of the main hurdles in low-power applications. Power switches enable power gating functionality, i.e., one or more parts of the SOC can be powered-off during standby mode leading in this way to savings in the overall SOC's power consumption. In this paper, we present a circuit and a method to test power switches. The proposed method allows testing of on/off fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Recent research has reported a number of DFT solutions to test power-switches when considering the two possible type of faults: stuck-open and stuck-short [3], [4]. The first DFT solution is reported in [3], and is used to test power switches in both fine-grain and coarse-grain designs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has reported a number of DFT solutions to test power-switches when considering the two possible type of faults: stuck-open and stuck-short [3], [4]. The first DFT solution is reported in [3], and is used to test power switches in both fine-grain and coarse-grain designs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In coarse-grain design style, power switches are divided into segments and the number of power switches per segment has a trade-off between area overhead, test time and precision in identifying faulty transistors [5], [9], [10]. This is shown in Table I, where for each design, we varied segment size from 5 to 30, and evaluated diagnosis accuracy using a fixed test frequency.…”
Section: Analysis Of Segment Size and Test Frequencymentioning
confidence: 99%
“…It is critical to silicon debugging, yield analysis and for improving subsequent manufacturing cycle [6]- [8]. Recent research has reported a number of DFT solutions to test power-switches when considering the two possible type of faults: stuck-open and stuck-short [5], [9]- [11]. Stuck-open fault models a physical scenario, where the drain or source of a transistor is disconnected leading to a faulty transistor behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, this is done in sequence and takes some time to get a power domain to its stable state. Many switches are used for given power domain and assembled in "fault-tolerant" scheme [20]. A defective switch (stuck-ON/OFF) usually results in performance degradation.…”
Section: Test Of Power Management Structuresmentioning
confidence: 99%